Body Metabolism and Exercise - Pokorski, Mieczyslaw (Advances in Experimental Medicine and Biology,, 2015)
The dynamics of body metabolism are changed in the disease process and interact with physical activity. The alteration of metabolism and its consequences raise the need for simple and reliable methods for assessment of body composition. The chapters aim to investigate various interacting components converging on metabolic changes in lung and muscle tissues taking into consideration the drug effects. The effects of exercise and nutritional status are dealt with at a great extent.